Rola materiałów legislacyjnych w porządku prawnym - Tobor, Zygmunt (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Information originating from legislative process plays a significant role in the system of law. Not only in the process of interpretation of legal texts, but also in many other areas. The presented article describes different possibilities of usage of legislative history. The aforementioned requires good knowledge of the legislative process itself, as well as the ability to distinguish reliable information from information that cannot be regarded as reliable.
Keywords: proces legislacyjny; historia prawodawstwa; system prawa; interpretacja tekstów prawniczych